The paracrine effects of adipocytes on lipid metabolism in doxorubicin-treated triple negative breast cancer cells - Ilze Mentoor (Taylor & Francis Group, 2021)
Adipocytes in the breast tumour microenvironment promotes acquired treatment resistance. We used an in vitro adipocyte-conditioned media approach to investigate the direct paracrine effects of adipocyte secretory factors on MDA-MB-231 breast cancer cells treated with doxorubicin to clarify the underlying treatment resistance mechanisms. Cell-viability assays, and Western blots were performed to determine alterations in apoptotic, proliferation and lipid metabolism protein markers. Free fatty acids (FFA) and inflammatory markers in the collected treatment-conditioned media were also quantified. Adipocyte secretory factors increased the cell-viability of doxorubicin-treated cells (p < 0.0001), which did not correspond to apoptosis or proliferation pathways. Adipocyte secretory factors increased the protein expression of hormone-sensitive lipase (p < 0.05) in doxorubicin-treated cells. Adipocyte secretory factors increased the utilization of leptin (p < 0.05) and MCP-1 (p < 0.01) proteins and possibly inhibited release of linoleic acid by doxorubicin-treated cells (treatment-conditioned media FFA profiles). Adipocyte secretory factors induced doxorubicin treatment resistance, by increasing the utilization of inflammatory mediators and inhibiting the release of FFA by doxorubicin-treated cells. This further promotes inflammation and lipid metabolic reprogramming (lipid storage) in the tumour microenvironment, which breast cancer cells use to evade the toxic effects induced by doxorubicin and confers to acquired treatment resistance.